New immunomodulatory steroidal alkaloids from Sarcococa saligna. (December 2015) - Iqbal, Naveed; Adhikari, Achyut; Kanwal, Nayab; Abdalla, Omer Mohamed; Mesaik, M. Ahmed; Musharraf, Syed Ghulam
Graphical abstract: Highlights: Four steroidal alkaloids were isolated and characterized from the Sarcococa saligna. Two were found to be new. Immunomodulatory activities of new compounds were also evaluated. Compound 1 showed inhibition (95%) of T-cell proliferation and IL-2 inhibition (IC50 = 1.6 μg/mL). Abstract: Two new steroidal alkaloids, (20 S )-(bennzamido)-3β-( N, N -dimethyamino)-pregnane (1 ), and (20 S )-(bennzamido)-pregnane-3-one- (2 ), and two known steroidal alkaloids, pachysanaximine A (3 ) and 3β, 20α-diacetamido-5α-pregnane (4 ) were isolated from the whole plant of Sarcococca saligna . The structures of these compounds were identified with the help of spectroscopic techniques while spectra for known compounds were compared with spectra reported in literature. The immunomodulatory potential of the new compounds were found to be significant and dose dependent. Compound1 showed inhibition of T cells proliferation at 10 μg/mL (95%), and inhibition of IL-2 production with an IC50 = 1.6 μg/mL.